RFID Tracking of Sublethal Effects of Two Neonicotinoid Insecticides on the Foraging Behavior of Apis mellifera - Schneider, Christof W. (Public Library of Science, 2012)

(untitled)
The development of insecticides requires valid risk assessment procedures to avoid causing harm to beneficial insects and especially to pollinators such as the honeybee Apis mellifera. In addition to testing according to current guidelines designed to detect bee mortality, tests are needed to determine possible sublethal effects interfering with the animal's vitality and behavioral performance. Several methods have been used to detect sublethal effects of different insecticides under laboratory conditions using olfactory conditioning. Furthermore, studies have been conducted on the influence insecticides have on foraging activity and homing ability which require time-consuming visual observation. We tested an experimental design using the radiofrequency identification (RFID) method to monitor the influence of sublethal doses of insecticides on individual honeybee foragers on an automated basis. With electronic readers positioned at the hive entrance and at an artificial food source, we obtained quantifiable data on honeybee foraging behavior. This enabled us to efficiently retrieve detailed information on flight parameters. We compared several groups of bees, fed simultaneously with different dosages of a tested substance. With this experimental approach we monitored the acute effects of sublethal doses of the neonicotinoids imidacloprid (0.15–6 ng/bee) and clothianidin (0.05–2 ng/bee) under field-like circumstances. At field-relevant doses for nectar and pollen no adverse effects were observed for either substance. Both substances led to a significant reduction of foraging activity and to longer foraging flights at doses of ≥0.5 ng/bee (clothianidin) and ≥1.5 ng/bee (imidacloprid) during the first three hours after treatment. This study demonstrates that the RFID-method is an effective way to record short-term alterations in foraging activity after insecticides have been administered once, orally, to individual bees. We contribute further information on the understanding of how honeybees are affected by sublethal doses of insecticides.